2004
DOI: 10.1055/s-2004-822321
|View full text |Cite
|
Sign up to set email alerts
|

A Simple One-Pot Synthesis of 2,6-Disubstituted 4-(Polyfluoroalkyl)pyridines and -pyrimidines by Reaction of 2-Polyfluoroalkylchromones with Aromatic Methyl Ketimines and Amidines

Abstract: The reaction of 2-polyfluoroalkylchromones with ketimines, derived from aromatic methyl ketones and isopropylamine, gives 2,6-diaryl-4-polyfluoroalkylpyridines in moderate to low yields. Benzamidine and guanidine also react with 2-polyfluoroalkylchromones to afford the corresponding 2,6-disubstituted 4-polyfluoroalkylpyrimidines.Much attention has been given to the chemistry of R F -containing N-heterocycles, because they find wide use in various areas of industry, medicine, and agriculture due to their unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…During the last decade Sosnovskikh [128,[194][195][196][197][198][199][200][201] and his group continued to devote great attention to the chemistry of 2-(polyhaloalkyl)chromones (2-R F -chromones) 185, particularly 2-(polyfluoromethyl)chromones (2-CF 3 -chromones) [52]. Some of their possible reactions are depicted in (Scheme 60): the reaction with ketimines leading to compounds 186-189 [194,196,198]; with acetophenones in the presence of lithium diisopropylamide to give 2-aroylmethyl-2-R F -chromanones 190 [197]; and a novel annulation reaction with salicylaldehydes in the presence of piperidine that constituted a direct route to chromeno [2,3-b]chromen-11-ones 191 by a tandem intermolecular oxa-Michael addition and subsequent intramolecular Mannich condensation [195].…”
Section: Reactivity Of Halomethylchromonesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade Sosnovskikh [128,[194][195][196][197][198][199][200][201] and his group continued to devote great attention to the chemistry of 2-(polyhaloalkyl)chromones (2-R F -chromones) 185, particularly 2-(polyfluoromethyl)chromones (2-CF 3 -chromones) [52]. Some of their possible reactions are depicted in (Scheme 60): the reaction with ketimines leading to compounds 186-189 [194,196,198]; with acetophenones in the presence of lithium diisopropylamide to give 2-aroylmethyl-2-R F -chromanones 190 [197]; and a novel annulation reaction with salicylaldehydes in the presence of piperidine that constituted a direct route to chromeno [2,3-b]chromen-11-ones 191 by a tandem intermolecular oxa-Michael addition and subsequent intramolecular Mannich condensation [195].…”
Section: Reactivity Of Halomethylchromonesmentioning
confidence: 99%
“…Some of their possible reactions are depicted in (Scheme 60): the reaction with ketimines leading to compounds 186-189 [194,196,198]; with acetophenones in the presence of lithium diisopropylamide to give 2-aroylmethyl-2-R F -chromanones 190 [197]; and a novel annulation reaction with salicylaldehydes in the presence of piperidine that constituted a direct route to chromeno [2,3-b]chromen-11-ones 191 by a tandem intermolecular oxa-Michael addition and subsequent intramolecular Mannich condensation [195].…”
Section: Reactivity Of Halomethylchromonesmentioning
confidence: 99%
“…we reported that 2-(trifluoromethyl)chromones serve as 1,3dielectrophilic units to afford trifluoromethylated pyrazoles, isoxazoles, dihydrothienocoumarins, [8] pyridines, pyrimidines, [9] benzenes, [10] and benzo[c]coumarins [11] upon treatment with 1,2-and 1,3-dinucleophiles such as hydrazines, hydroxylamine, ethyl mercaptoacetate, amidines, methyl ketimines, and ethyl cyanoacetate, respectively. The last domino reaction involves ethyl cyanoacetate, which behaves as a synthetic equivalent of 1,3-dicyanoacetone with two nucleophilic centers.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ = 1.12 (t, J = 7.3 Hz,9 H, 3ϫ Me), 2.84 (q, ) ppm.19 F NMR (376 MHz, CDCl 3 ): δ = 103.4 (s, CF 3 ) ppm. 127-128°C (dec.), yellow powder.…”
mentioning
confidence: 99%
“…We recently reported 1,2 that aromatic methyl ketimines, capable of reacting with electrophilic substrates as 1,3-C,N-dinucleophiles through their enamine tautomeric form, underwent conjugate addition to 2-polyfluoroalkylchromones 1. This reaction can be followed by the pyrone ring opening and intramolecular cyclization at the keto group to give 2,6-diaryl-4-(polyfluoroalkyl)pyridines in moderate yields.…”
mentioning
confidence: 99%